Pengaruh Struktur Modal dan Profitabilitas terhadap Likuiditas Perusahaan: Analisis Debt to Equity Ratio dan Return on Assets terhadap Current Ratio - Ahmad Afendy Susanto; Junirin Junirin; Sofia Ulfa; Rasyiid Yoga Pradita; Sudarmin Sudarmin (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of capital structure and profitability on company liquidity. The variables used in this research include Debt to Equity Ratio (DER) as an indicator of capital structure, Return on Assets (ROA) as an indicator of profitability, and Current Ratio (CR) as an indicator of liquidity. The research employed a quantitative approach using descriptive and verificative methods. The data used were secondary data obtained from financial statements with a total sample of 36 observations selected through purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS 25 software. The results show that DER and ROA partially and simultaneously have a positive and significant effect on CR. The coefficient of determination (R²) value of 0.915 indicates that 91.5% of the variation in company liquidity can be explained by capital structure and profitability variables, while the remaining 8.5% is influenced by other variables outside the research model. Furthermore, ROA is proven to have a more dominant influence on CR compared to DER. These findings indicate that improving company profitability plays a crucial role in strengthening the company's ability to meet its short-term obligations. Therefore, companies are recommended to optimize asset utilization to increase profitability while managing debt proportionally in order to maintain sustainable liquidity stability.